Harnessing centred identity transformation to reduce executive function burden for maintenance of health behaviour change: the Maintain IT model. Issue 3 (3rd July 2018) - Caldwell, Ann E.; Masters, Kevin S.; Peters, John C.; Bryan, Angela D.; Grigsby, Jim; Hooker, Stephanie A.; Wyatt, Holly R.; Hill, James O.
ABSTRACT: The inability to produce sustainable lifestyle modifications (e.g., physical activity, healthy diet) remains a major barrier to reducing morbidity and mortality from prevalent, preventable conditions. The objective of this paper is to present a model that builds on and extends foundational theory and research to suggest novel approaches that may help to produce lasting behaviour change. The model aims to integrate factors not typically examined together in order to elucidate potential processes underlying a shift from behaviour initiation to long-term maintenance. The central premise of the Maintain IT model builds on approaches demonstrating that in-tact executive function (EF) is critical for health behaviour initiation, for more complex behaviours beyond initiation, and in unsupportive environments and circumstances, but successful recruitment of EF is effortful and prone to error. Enduring changes are more likely if the underlying cognitive processes can become less effortful (non-conscious, automatic). The Maintain IT model posits that a centred identity transformation is one path leading to less effortful processing and facilitating successful recruitment of EF when necessary over the long term, increasing the sustainability of health behaviour change. A conceptual overview of the literature supporting the utility of this integrative model, future directions, and anticipated challenges are presented.